Pre-operative assessment of internal mucosal rectal prolapse in internal hemorrhoids: technical details and results from a single institution - Percalli, Luigi; Passalia, Luigi; Pricolo, Renato; Riccò, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Background: The aim of the study was to assess safety and efficacy of pre-operative assessment for internal mucosal rectal prolapse (IMRP) in internal hemorrhoids, in order to achieve a tailored transanal stapled surgery. Methods: All consecutive patients (January 2011 to December 2014; age 18-80 years), affected by prolapses with II-IV degrees hemorrhoids that underwent Longo procedure with EEA® Auto Suture stapler (Covidien) were included in the present study. Results: A total of 100 consecutive patients (38 females) were enrolled in the study. Preoperative Visual Analogue Scale pain assessment was 7.33±2.68. The mean duration of the procedure was 34.1±17.8 min, and the median hospital stay was 2 days (range 2-6). No major complication occurred, including relapses of mucosal prolapse. Preoperative prolapse measurement with EEA® EEA® Auto Suture stapler (2.3±0.5 cm) was well correlated direct assessment (2.4±0.6, p